2018
DOI: 10.1136/bmjopen-2017-019063
|View full text |Cite
|
Sign up to set email alerts
|

Period prevalence, risk factors and consequent injuries of falling among the Saudi elderly living in Riyadh, Saudi Arabia: a cross-sectional study

Abstract: ObjectivesApproximately 28% to 35% of people aged 65 and over fall each year. The consequent injuries of falls are considered a major public health problem. Falls account for more than half of injury-related hospitalisations among old people. The aim of this study was to measure a 1-year period prevalence of falling among old people in Riyadh, Saudi Arabia. In addition, this study described the most common risk factors and consequent injuries of falls.Setting and participantsA cross-sectional survey was carrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
67
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(75 citation statements)
references
References 33 publications
6
67
1
1
Order By: Relevance
“…Several studies assessed the prevalence of falls in older adults, and the related fall risk factors. 20 , 21 , 22 However, few studies addressed this issue in the Arab countries 20 , 23 , 24 and to the authors’ best knowledge there is lack of such studies in UAE. Therefore, in the present study we aimed to assess the prevalence of falls in the past two years among older adults aged 60 years and above and to determine the risk factors associated with falls.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies assessed the prevalence of falls in older adults, and the related fall risk factors. 20 , 21 , 22 However, few studies addressed this issue in the Arab countries 20 , 23 , 24 and to the authors’ best knowledge there is lack of such studies in UAE. Therefore, in the present study we aimed to assess the prevalence of falls in the past two years among older adults aged 60 years and above and to determine the risk factors associated with falls.…”
Section: Discussionmentioning
confidence: 99%
“…It may be attributed to only 4.9% of the population above 60 years in KSA [ 3 ]. The present study is a good study that reports fall-related injuries irrespective of age and gender.…”
Section: Discussionmentioning
confidence: 99%
“…Accidental falls impose significant morbidity, mortality and socioeconomic burden, rendering them as the second leading cause of hospitalization for all age groups around the world [ 2 ]. In the Kingdom of Saudi Arabia (KSA), approximately 28-35% people aged ≥65 years experience falls each year [ 3 ]. Fall-related injuries are the most common accidental injuries among children and adolescents in Riyadh [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a review of recent reports, Vieira et al [36] reported that in a random sample of 1451 people aged ≥60 years in Brazil, the adjusted odds ratio for the incidence of falls was higher among people with 4-7 years of education (adjusted odds ratio, 1.40; 95% confidence interval, 1.09-1.80) and uneducated people (adjusted odds ratio, 1.47; 95% confidence interval, 1.09-1.80) in comparison to people with ≥12 years of education. In addition, a study of a random sample of 1182 people aged ≥60 years in Saudi Arabia by Almegble et al [37] revealed a higher adjusted odds ratio for the incidence of falls among middle school graduates and uneducated people in comparison to university graduates.…”
Section: Level Of Education and Falls And Related Bone Fracturesmentioning
confidence: 99%